Social psychology of exercise and sport - Hagger, Martin (Applying social psychology., 2005)
The "Social Psychology of Exercise and Sport" examines the role that social psychology has in the explanation of exercise and sport behavior. It devotes considerable attention to key social psychological issues within the two disciplines, exercise behavior for health reasons, and the behavior of competitive sport participants and the spectators of elite sport. The book focuses on a narrow range of selected topics and provides comprehensive, in-depth, and analytical coverage using social psychology as a framework